Sustainable Materials and their Contribution to the Sustainable Development Goals (SDGs): A Critical Review Based on an Italian Example - Elza Bontempi; Giampiero P. Sorrentino; Alessandra Zanoletti; Ivano Alessandri; Laura E. Depero; Andrea Caneschi (Molecules, 2021)
The Sustainable Development Goals (SDGs) have been proposed to give a possible future to humankind. Due to the multidimensional characteristic of sustainability, SDGs need research activities with a multidisciplinary approach. This work aims to provide a critical review of the results concerning sustainable materials obtained by Italian researchers affiliated to the National Interuniversity Consortium of Materials Science and Technology (INSTM) and their contribution to reaching specific indicators of the 17 SDGs. Data were exposed by using the Web of Science (WoS) database. In the investigated period (from 2016 to 2020), 333 works about sustainable materials are found and grouped in one of the following categories: chemicals (33%), composites (11%), novel materials for pollutants sequestration (8%), bio-based and food-based materials (10%), materials for green building (8%), and materials for energy (29%). This review contributes to increasing the awareness of several of the issues concerning sustainable materials but also to encouraging the researchers to focus on SDGs’ interconnections. Indeed, the mapping of the achievements can be relevant to the decision-makers to identify the opportunities that materials can offer to achieve the final goals. In this frame, a “Sustainable Materials Partnership for SDGs” is envisaged for more suitable resource management in the future.